Improving the Efficiency of Construction of High-Rise Monolithic Reinforced Concrete Buildings with the Introduction of Innovative Technologies and Technologies - A.Farzaliyev, S; ., .; ., . (International Journal of Engineering and Technology, 2018)
Innovations' application of techniques and technologies to modern construction production, along with the reduction of manual labor, also boosts its technical and economic performance. Construction production is one of the fields in the country that plays the most important role and reflects the dynamics of the development of the economy in itself.  In our country, the issue of organizing a cheap housing market has an importance among  a number of socio-economic issues. The programmes adopted in this direction and the initiatives  dealing with the improvement of housing conditions for people from a number of categories are evident proof of this. And this, in its  turn, requires the solution of a number of organizational and technological problems of construction work carried out by monolithic reinforced concrete structures before both the designers and builders. The article explores the ways of timely commissioning of high-rise monolithic reinforced concrete buildings, improving the organization of work, and increasing the technological efficiency to reduce the cost of construction products. It was determined that during the reinforcement of monolithic reinforced concrete structures, automation of works will reduce labor costs, material consumption, product cost and construction time, while technological efficiency is increasing.